EFFORTS OF TAIWAN'S NEW SOUTHBOUND POLICY IN SUPPORTING THE ECONOMY THROUGH TAIWAN'S EXPORT COOPERATION WITH ASEAN DURING THE COVID-19 PANDEMIC - Angela Nur Eka (UNIDA GONTOR, 2022)
The Covid-19 pandemic attacked the world and had a very extraordinary impact. This pandemichas changed the order of economic and health aspects and changes in people's social interactions.Taiwan's exports to ASEAN itself were affected so that they experienced a decline, especially in2020 the export value decreased by 1.3 percent due to the Covid-19 pandemic, several causes ofwhich were a decrease in international prices for oil and gas products and steel products. TheNew Southbound Policy is one of Taiwan's strategies towards Taiwan's economic and traderelations with the aim of redefining Taiwan's role in the development of the Asian region. Thisresearch aims to find out the efforts made by Taiwan's New Southbound Policy in boosting theeconomy through Taiwan's export cooperation with ASEAN during the Covid-19 Pandemic. Themethod used in this research is descriptive qualitative method. Data collection techniques wereobtained by literature study, namely in the form of books, journals, and other literature related tothis research. In addition, this study uses the concept of foreign policy and national interest as aframework for research analysis. The results of this study indicate that Taiwan's foreign policy,namely the New Southbound Policy, was formulated to improve Taiwan's internal economy andcan be recognized internationally. During the Tsai Ing wen era, Taiwan reinstated the NewSouthbound Policy because Taiwan had national interests, especially in improving the exportsector's national economy. With this policy, Taiwan succeeded in increasing the value of exportsto ASEAN during the pandemic